Do reported attitudes towards Immigrants predict ethnic discrimination? - Magnus Carlsson; Stefan Eriksson (Uppsala University, Department of Economics, 2012)
Reported attitudes towards immigrants are sometimes used as a proxy for ethnic discrimination. However, there is little empirical evidence of a link between attitudes and discrimination. In this paper, we use survey data on people's attitudes towards immigrants combined with data on ethnic discrimination from a field experiment in the Swedish housing market to re-examine this issue. We find clear evidence of a link between reported attitudes towards immigrants and the extent of ethnic discrimination at the municipality level. Thus, in contrast to most prior studies, our results suggest that reported attitudes may be a useful proxy for ethnic discrimination.
urn:nbn:se:uu:diva-169396
Keywords: C93; J15; R39; 330; Attitudes; Ethnic discrimination; Field experiments; Housing market; Ethnische Diskriminierung; Meinung; Feldforschung; Wohnungsmarkt; Schweden